2022
DOI: 10.1002/cssc.202201183
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Carbon Dioxide Adsorption, Activation and Hydrogenation to Methanol using Transition Metal Carbides

Abstract: The inevitable emission of carbon dioxide (CO 2 ) due to the burning of a substantial amount of fossil fuels has led to serious energy and environmental challenges. Metal-based catalytic CO 2 transformations into commodity chemicals are a favorable approach in the CO 2 mitigation strategy. Among these transformations, selective hydrogenation of CO 2 to methanol is the most promising process that not only fulfils the energy demands but also re-balances the carbon cycle. The investigation of CO 2 adsorption on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 319 publications
0
11
0
Order By: Relevance
“…They also stated that the adsorbed MMC configuration is more active and susceptible to hydrogenation processes. [22] Chen et al explored the mechanism of CO 2 activation on TMCs through theoretical calculations and concluded that the binding energy of TMCs with O (OBE) played a considerable role in CO 2 hydrogenations. [25] When TMCs had a high OBE value, CO 2 molecules were prone to be directly dissociated to generate CO (*CO 2 →*CO+*O).…”
Section: Advantages Of Tmcs In Co 2 Hydrogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…They also stated that the adsorbed MMC configuration is more active and susceptible to hydrogenation processes. [22] Chen et al explored the mechanism of CO 2 activation on TMCs through theoretical calculations and concluded that the binding energy of TMCs with O (OBE) played a considerable role in CO 2 hydrogenations. [25] When TMCs had a high OBE value, CO 2 molecules were prone to be directly dissociated to generate CO (*CO 2 →*CO+*O).…”
Section: Advantages Of Tmcs In Co 2 Hydrogenationmentioning
confidence: 99%
“… 1)TMCs are electrophilic, so they exhibit unique adsorption capacity and catalytic performance for molecules with weak oxidation properties. [ 7f,22–24 ] In particular, the adsorption strength of TMCs for CO 2 is neither too strong nor too weak because of the unique atomic arrangement between C and their parent metals. According to the Sabatier principle, TMCs could exhibit better potential as ideal and powerful CO 2 hydrogenation catalysts because of the appropriate CO 2 activation ability than metals and metal oxides.…”
Section: Advantages Of Tmcs In Co2 Hydrogenationmentioning
confidence: 99%
“…The conversion of CO 2 into value-added chemicals may be a crucial approach to mitigate climate change and reduce reliance on fossil fuels. 1 Several reactions, such as the reverse water gas shift (CO 2 + H 2 → CO + H 2 O), dry reforming of methane (CO 2 + CH 4 → 2CO + 2H 2 ), and selective hydrogenation (CO 2 + 3H 2 → CH 3 OH + H 2 O), have been extensively investigated. 2,3 To this end, noble metals and copper-based catalysts are required due to the thermodynamic stability and kinetic inertness of CO 2 molecules, while noble metals are of high cost, and copper-based catalysts are easily deactivated at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dioxide (CO 2 ) and methane (CH 4 ) are among the worst greenhouse gases and main contributors to global warming and climate change. Both molecules are highly stable, are nonpolar, and display a low reactivity. New initiatives emphasize the need to design and optimize processes for the trapping, storage, and conversion of CO 2 and CH 4 . These processes involve three essential components: (1) A reactive center that binds and activates the CO 2 or CH 4 molecule, (2) a surrounding phase with reactants or solvents, and (3) a source of thermal, electrical, or photochemical energy. Catalytic conversion of CO 2 or CH 4 to chemicals and fuels is a “two birds, one stone” approach toward solving the climate change problem and energy demand-supply deficit in the modern world. Conversion to oxygenates or light alkanes are promising processes for a large scale utilization of CO 2 and CH 4 . These conversions are hampered by challenges associated with the low activity and selectivity of currently used catalysts. In recent years, transition metal carbides (TMCs) have emerged as useful materials for the activation and transformation of CO 2 and CH 4 . …”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering work of Levy and Boudart, where the hydrogenation ability of TMCs was described as comparable to that of Pt-group elements, these materials have been the focus of many studies in catalysis. , Transition metal carbides can display a unique combination of the physical properties characteristic of noble metals and ceramics. , Many TMCs are good electrical and thermal conductors while possessing ultrahardness and very high melting points. , The degree of ionicity in a metal–carbon bond is much smaller than in a metal-oxide bond, opening the possibility for different catalytic properties. , In a metal carbide, metal and carbon centers can participate in the binding an activation or CO 2 or CH 4 . ,, The formation of C–C or CC bonds can occur after adsorbing CO 2 or CH x fragments on a metal carbide. , The carbon/metal ratio is an important variable that can be used to tune the breaking of one or two hydrogen bonds in the CO 2 molecule and favor the selectivity during hydrogenation toward oxygenates or alkanes. , For a given carbon/metal ratio, different catalytic properties have been seen for bulk, two-dimensional (2D) and nanostructure systems. ,,, Furthermore, transition metal carbide surfaces can act as supports, having an useful ability to modify the catalytic properties of supported metals not seen in the case of metal oxide substrates. ,,, …”
Section: Introductionmentioning
confidence: 99%